Território entremeado: espaços da memória e travessias identitárias em Ponte do galo e Órfãos do Eldorado - BONFIM, Maissa Taís da Silva (2020)
In the present work, we aim to analyze the processes of identity formation in the Amazon, based on the comparative study of the works Ponte do Galo (1971) by Dalcídio Jurandir and Órfãos do Eldorado (2008) by Milton Hatoum. For this, with the thematic link between memory and identity, we intend to show how the relations and displacements of the protagonist subjects of these narratives reflect a pluralistic and heterogeneous Amazonian territory. Conscious of the existence of a literary tradition of Amazonian representation, we support researchers such as Ana Pizarro (2012), Marli Furtado (2002), Edilson Pantoja (2006), José Alonso Freire (2006), Maria Zilda Cury (2007), with the objective of understanding how the works of Dalcídio Jurandir and Milton Hatoum move against this logic, destabilizing concepts associated with a notion of full identity and one. We also propose, from the theoretical perspective of Stuart Hall, in his book The cultural identity in postmodernity (2015), a reading of the construction of the identities of the characters in the narratives that, articulated to a temporal dimension of these subjects, are always put in question. In view of Hall's notion of a crisis of identity values, whose references are in the process of fragmentation, we understand that both Jurandir and Hatoum not only reconstruct local identity marks, but they also smash these marks through the condition in which their characters are placed as decentred subjects, as seen in the context of postmodernity.